Analysis Factor Initiated Early Breastfeeding, Husband Support and Promotion of Formula Milk to Failure of Exclusive Breastfeeding: Research Study at Turi Health Center, Lamongan Regency - Asyaul Wasiah; Koesnadi Koesnadi; Indasah Indasah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Various studies show that the coverage of exclusive breastfeeding in Indonesia is still very low. Exclusive breastfeeding is very important for the survival of the baby because it contains growth factors and antibody substances. If breast milk is not given exclusively, the immune system's maturation process will be disrupted and cause the baby to get infected easily. The purpose of this study was to find out the most dominant factors affecting the failure of exclusive breastfeeding at Turi Health Center, Lamongan Regency. This research is descriptive descriptive analysis with cross sectional design. A sample of 132 mothers who have babies aged 6-12 months with the Simple Randem Sampling technique, questionnaire instruments, data analysis with the Logistic Regression test. Most of the mothers did not initiate early breastfeeding, namely 78 (59.1%), got enough husband support 80 respondents (60.6%) and interested in promoting formula milk as many as 74 respondents (56.1%). For partial test Early breastfeeding initiation has a Sig 0.003 value, husband's support for Sig 0.004 and promotion of formula milk Sig 0.001. The results of the analysis of the most dominant variable on the failure of Exclusive ASI were husband's support with a value of OR 1.868. It is expected to increase counselin g and information about the Initiation of Early Breastfeeding and Exclusive Breastfeeding for pregnant women and mothers having babies. As well as being more selective in accepting all forms of promotion of formula milk from various promotional media